Kajian Pemasaran Beras Merah Di Wilayah Perbatasan (Entikong) Kabupaten Sanggau Provinsi Kalimantan Barat - Imelda, Enna Dardanella, Ani Muani, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
Enna Dardanella “Brown Rice Marketing Studi within the Border Region (Entikong) in Sanggau Regency, West Kalimantan Province”, under the guidence of Ir. Ani Muani, MS and Imelda, SP. M.Sc. This study aims to (1) understand the marketing functions performed by each marketing agencies, (2) determine how many pattern of brown rice marketing channels exist (3) determine which channels is the most efficient marketing channels (4) understand the marketing structure of brown rice in the border region.The results showed (1) exchange function (sales and purchases) and physical function (packaging, transportation, and storage) is done by the producers (farmers), collectors, retailers. At the facility function, brown rice producers only perform two functions, the risk and cost functions, while collectors and retailers perform all the existing functions. (2) there are two types of brown rice marketing patterns, the first pattern is domestic pattern and the second pattern is of trans-border marketing pattern. (3) the most efficient brown rice marketing channel is channel I which consist of Brown Rice Producers - Consumers with 100 % farmer's share and 40.67 % profitability index. (4) the marketing structure occurred in the domestic pattern and trans-border marketing pattern of brown rice is also a monopolistic market.Keywords: Brown Rice, Marketing Function, Marketing Margin, Farmer’s Share, and Profitability Index.